2022
DOI: 10.1186/s12866-022-02638-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microecology to different cropping practice under Bupleurum chinense cultivation

Abstract: The effects of cropping practices on the rhizosphere soil physical properties and microbial communities of Bupleurum chinense have not been studied in detail. The chemical properties and the microbiome of rhizosphere soil of B. chinense were assessed in the field trial with three cropping practices (continuous monocropping, Bupleurum-corn intercropping and Bupleurum-corn rotation). The results showed cropping practices changed the chemical properties of the rhizosphere soil and composition, structure and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These eutrophic bacteria can mineralize soil nutrients, enhance the absorption of nutrients by plants, and promote plant growth ( Tian et al, 2020 ). This is similar to observations from the dominant rhizosphere communities of other medicinal plants, such as healthy Panax notoginseng and Bupleurum chinense ( Tan et al, 2017 ; Liu et al, 2022 ). Regardless of the difference in experimental site or variety (strain), Proteobacteria was the dominant phylum in the rhizosphere of A. dahurica var.…”
Section: Discussionsupporting
confidence: 88%
“…These eutrophic bacteria can mineralize soil nutrients, enhance the absorption of nutrients by plants, and promote plant growth ( Tian et al, 2020 ). This is similar to observations from the dominant rhizosphere communities of other medicinal plants, such as healthy Panax notoginseng and Bupleurum chinense ( Tan et al, 2017 ; Liu et al, 2022 ). Regardless of the difference in experimental site or variety (strain), Proteobacteria was the dominant phylum in the rhizosphere of A. dahurica var.…”
Section: Discussionsupporting
confidence: 88%
“…While the importance of crop rotation for reducing pathogen host-crop incidence is acknowledged [ 4 ] less is known about the indirect impacts of canola frequency on the broader soil and plant microbiome and how this subsequently affects soil nutrient cycling and uptake. Compared to monoculture, diverse rotations have higher levels of nutrient cycling [ 5 ], increases in bioavailable nitrogen, soil organic matter, and available potassium [ 6 ], and appear to have broader soil microbial metabolic capabilities, perhaps owing to a greater diversity of residue input types [ 7 , 8 ]. Canola is known to have diverse and abundant root and rhizosphere microbiomes [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that preceding crop cultivation could significantly affect the physicochemical properties of tobacco-plant soil, overall depends on the crop types. The cropping practices changed the chemical properties of the rhizosphere soil and the composition, status, and diversity of the rhizosphere microbial communities ( Liu et al, 2022 ). Meanwhile, the two-factor correlation network results showed that NH 4 + -N and NO 3 − -N were the environmental factors with a high correlation with bacteria in the tobacco-planting soil.…”
Section: Discussionmentioning
confidence: 99%
“…A flame photometer determined the content of potassium in the soil sample. Soil pH was determined by a pH-4 portable pH meter (soil-to-water ratio 2.5:1) according to Liu et al (2022) .…”
Section: Methodsmentioning
confidence: 99%